EXTREME VULNERABILITY EVALUATION IN INTEGRATED POTATO SUPPLY CHAINS: SCOR APPROACH AND LIKELIHOOD-IMPACT MAPPING - Ujang Apriansyah; Endang Tri Astutiningsih; Ashrul Tsani; Zhang Li (Journal Markcount Finance, 2026)
This study quantifies the extreme vulnerability of the integrated potato supply chain at PT Fujitake Shouten, Nagasaki, Japan, amidst intersecting macroeconomic, demographic, and climate crises. By integrating the Supply Chain Operations Reference (SCOR) model with a Likelihood-Impact matrix, this research systematically prioritized 40 operational risk events validated through stakeholder consensus to assess the systemic fragility of fresh produce logistics. Empirical results reveal a dominant concentration of threats within the “High” and “Very High” risk categories, confirming an operational environment with a near-zero margin of error. The analysis identified a critical domino effect where rural labor shortages necessitate rough mechanical harvesting, causing physical tuber damage that accelerates metabolic respiration and spoilage during cold storage, ultimately disrupting financial liquidity and downstream retail performance. To mitigate these cascading failures, the study provides a data-driven framework where specific interventions notably precision cold-chain temperature management and visual quality controls are directly linked to risk reduction. These findings offer an actionable strategy for agribusiness entities to transition from reactive measures to proactive resilience, effectively stabilizing cash-to-cash cycles in vertically integrated supply chains.